The Waqf Management: Perspective in Comparison - Mubaraq, Ahmad (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
Waqf is an important instrument to improve welfare. Traditionally, the object of waqf is land. However, as civilization develops, waqf objects also need innovation because of limited land. This innovation also needs to be balanced with quality management. This study compares perspective of waqf management by three institutions in Province Yogyakarta Indonesia. They are Nahdlatul Ulama, Muhammadiyah, and Badan Wakaf Indonesia. This study uses explorative qualitative techniques. Data was obtained from interviews and documentation. Data analysis by coding techniques (breaking coding, pivot coding and choir coding). The results of the study found that (a) the management of waqf by Nahdlatul Ulama has not been managed properly legally administrative; (b) the management waqf by Muhammadiyah has been managed legally administratively; (c) the management and utilization of waqf by the Badan Wakaf Indonesia is well managed legally.